Diagnosis of attention deficit hyperactivity disorder: much ado about something - Berger, Itai (The Israel Medical Association journal, 2011)
Attention deficit hyperactivity disorder (ADHD) is among the most prevalent chronic health disorders affecting school-age children. The disorder is the subject of much debate for several reasons, the major one being the diagnostic process, which in some aspects is unstructured and can be relatively easily biased. The impact of undiagnosed or misdiagnosed ADHD on the lives of many children can be severe. Therefore, it is important to understand the complexities of the diagnostic procedure in ADHD, including the cultural bias effect, the limitations of the DSM-IV-TR definitions, the effect of comorbid conditions on the diagnostic process, the gene-environment interaction, and the need to compose an objective, more accurate, and generally accepted diagnostic battery of tests. This review addresses the diagnostic difficulties of ADHD and considers some steps that would make ADHD a more easily identifiable disorder.